Os níveis séricos de calicreína plasmática e catepsina B estão associados com à fibrose hepática em pacientes com hepatite c crônica - Zanelatto, Alexia de Cassia Oliveira [UNIFESP] (2018)
Introduction. Hepatitis C Virus (Hcv) Is One Of The Leading Causes Of Chronic Liver Disease Worldwide, Where 85% Of Those Infected Have Some Degree Of Liver Fibrosis. Transforming Growth Factor-Beta 1 (Tgf-"1) Plays An Important Role In The Proliferation And Activation Of Hepatic Stellate Cells (Hsc) In The Process Of Inducing Liver Fibrosis. Cathepsin B (Cat B) And Plasma Kallikrein (Plk) Are Enzymes That Can Proteolytically Activate The Latent Form Of Tgf-"1 During Hepatic Fibrosis Induced By Hcv Infection. The Severity Of Hepatic Fibrosis Determines The Prognosis And Treatment Of Patients With Chronic Hepatitis C (Hcc). Objectives. Verify Whether Serum Levels Of Cat B And Plk Correlated With The Severity Of Hepatic Inflammation And Fibrosis In Patients With Chc Before And After Treatment With Interferon " With Ribavirin, And Could Serve Introduction. Hepatitis C virus (HCV) is one of the leading causes of chronic liver disease worldwide, where 85% of those infected have some degree of liver fibrosis. Transforming growth factorbeta 1 (TGFβ1) plays an important role in the proliferation and activation of hepatic stellate cells (HSC) in the process of inducing liver fibrosis. Cathepsin B (Cat B) and plasma kallikrein (PLK) are enzymes that can proteolytically activate the latent form of TGFβ1 during hepatic fibrosis induced by HCV infection. The severity of hepatic fibrosis determines the prognosis and treatment of patients with chronic hepatitis C (HCC). Objectives. Verify whether serum levels of Cat B and PLK correlated with the severity of hepatic inflammation and fibrosis in patients with CHC before and after treatment with interferon α with ribavirin, and could serve as new noninvasive biomarkers for the diagnosis of hepatic fibrosis. Methodology. Serum levels of Cat B and PKL were classified in patients with CHC, according to the METAVIR (N = 53) table, as well as in blood donors without HCV (N = 70). The different laboratory data were correlated with each other and with Cat B and PKL measures, using Pearson's coefficient to evaluate parametric data and Spearman's coefficient for nonparametric data. The sensitivity, specificity and diagnostic accuracy of Cat B and PKL were evaluated by the ROC curve, these results were compared with the performance of noninvasive biomarkers APRI and FIB4. Also, Cat B and PKL values were correlated with sustained virological response (SVR) in patients receiving interferonα + ribavirin, all with histological assessment of hepatic fibrosis prior to treatment (METAVIR). Results. Serum levels of Cat B (3.61 ± 0.26 U/ml) and PKL (3.77 ± 0.24 U/ml) were significantly higher (P <0.0001) in subjects with hepatic fibrosis ≥ F2 when compared to healthy subjects without hepatic fibrosis (1.61 ± 0.06 U/ml). In addition, we found that levels of Cat B and PLK were gradually elevated according to the severity of the liver fibrosis score. Cat B levels correlated strongly with serum PLK levels in CHC patients (r = 0.953, CI95% = 0,916 0,974, P <0.0001). According to the area under the ROC curve, levels of Cat B (AUROC = 0.99 ± 0.01) and PKL (AUROC = 0.99 ± 0.01) were significantly higher than APRI (AUROC = 0, 71 ± 0.05) and FIB4 (AUROC = 0.67 ± 0.06) to predict initial hepatic fibrosis (≥ F2) in patients with HCC. The cutoff value established for serum levels of Cat B ≥ 2.61 U / mL identifies with high precision the presence of inflammation and hepatic fibrosis in the ≥ A1F2 score in patients with HCV, as well as serum levels of Cat B < 2.61 U/ml identified the absence of hepatic lesion in the population (Sensitivity = 96%, Specificity = 95%). The cutoff value for serum PKL ≥ 2.9 U/ml accurately identifies the presence of inflammation and hepatic fibrosis in the ≥ A1F2 score in patients with HCV, such as serum PKL <2.9 U/ml identified absence of hepatic fibrosis in the population (Sensitivity = 96%, Specificity = 98%). Furthermore, the high concentration of Cat B (> 3.3 U/ml) in the serum of patients with HCV is able to predict the failure of treatment with interferon α associated with ribavirin. Conclusion. Serum levels of Cat B and PKL can be used as reliable biomarkers for the prediction of initial inflammation and hepatic fibrosis (≥ A1F2) in patients with HCV, as well as being reliable for excluding the diagnosis of liver fibrosis in the population. Serum cathepsin B levels may aid in the prediction of successful treatment of patients with interferon α + ribavirin.